Assessing Callous-Unemotional Traits in Chinese Detained Boys: Factor Structure and Construct Validity of the Inventory of Callous-Unemotional Traits - Zhang, Xintong; Shou, Yiyun; Wang, Meng-Cheng; Zhong, Chuxian; Luo, Jie; Gao, Yu; Yang, Wendeng (Frontiers in Psychology, 2019)
The Inventory of Callous-Unemotional Traits (ICU) was designed to evaluate multiple facets of Callous-Unemotional (CU) traits in youths. However, no study has examined the factor structure and psychometrical properties of the ICU in Chinese detained juveniles. The current study assesses the factor structure, internal consistency and convergent validity of the ICU in 613 Chinese detained boys. Confirmatory factor analysis results indicated that the original three-factor bifactor model with 24 items was an unacceptable fit for the data, however the 11-item shortened version of the ICU (ICU-11) with callousness and uncaring dimensions was the best fit. Moreover, the ICU-11 total score and factor scores had good and acceptable internal consistency and demonstrated comparable and better correlations with relevant external criteria (e.g., psychopathy, aggression and empathy). In conclusion, present findings have proved that the ICU-11 is a reliable and efficient instrument to replace the original ICU when assessing CU traits in the Chinese male detained juvenile sample.